Applying Algorithmic Thinking to Teaching Graphs of Functions For Students Through Geogebra - Doc, Nguyen Van; Giam, Nguyen Minh; Nam, Nguyen Thi Hoai; Thanh, Ngo Tu; Giang, Nguyen Thi Huong (Journal of Education For Sustainable Innovation, 2023)
Algorithmic thinking is a term that is of interest to many educators and teachers. Algorithmic thinking plays an important role not only in problem solving but also in solving real world problems. The article presents some concepts of algorithmic thinking; propose the process of applying algorithmic thinking to teaching function graphs for students through GeoGebra online, helping students to draw all functions in the fastest way. GeoGebra is integrated with algorithms used to graph any function online that students cannot do. GeoGebra is used effectively, interactively and actively supported by many students, students and teachers of Mathematics in the process of graphing functions and graphs in an intuitive and detailed way, thereby developing develop students' thinking.